The impact of innovation competitive advantage on product quality for sustainable growth among SMEs: An empirical analysis - Danjuma Tali Nimfa; Md Uzir Hossain Uzir; Livinus Nkuri Maimako; Bilal Eneizan; Ahmad Shaharudin Abdul Latiff; Sazali Abdul Wahab (International Journal of Business Science & Applied Management (IJBSAM), 2021)
Supported by the dynamic capabilities theory of the firm, this study considered innovation competitive advantage, product quality, and technology adoption as the core dynamic capabilities of manufacturing SMEs. The purpose of this study was to investigate the impact of two components of innovation competitive advantage, that is, customer preference and strategic business model, on product quality for sustainable growth among SMEs. It also examined the mediating effect of technology adoption on the relationship between innovation competitive advantage and product quality. Survey data was collected from 245 manufacturing SMEs in Nigeria and analysed using partial least squares structural equation modelling. The results revealed that customer preference does not directly affect product quality; however, technology adoption mediates the relationship between customer preference and product quality. The strategic business model was found to have a significant positive effect on product quality, Int. Journal of Business Science and Applied Management / Business-and-Management.org 40 and this relationship was mediated by technology adoption as well. This research recommends that manufacturing SME managers recognise that improving product quality through innovation competitive advantage strategies and technology adoption is advantageous for the sustainable growth of SMEs.
Keywords: 650; Innovation competitive advantage; Product quality; Customer preference; Strategic business model